Depletion of the LINC complex disrupts cytoskeleton dynamics and meiotic resumption in mouse oocytes - Luo, Yibo (Sci Rep, 2016)
The SUN (Sad-1/UNC-84) and KASH (Klarsicht/ANC-1/Syne/homology) proteins constitute the linker of nucleoskeleton and cytoskeleton (LINC) complex on the nuclear envelope. To date, the SUN1/KASH5 complex is known to function as meiotic-specific factors. In this study, gene-silencing methods were used to explore the roles of SUN1 and KASH5 in mouse oocytes after prophase. SUN1 was detected throughout the nucleus; however, KASH5 was dispersed through the cell. After germinal vesicle breakdown (GVBD), SUN1 and KASH5 migrated during spindle formation and localized to the spindle poles at the MII stage. Most oocytes were arrested at the germinal vesicle (GV) stage after depletion of either SUN1 or KASH5. The DNA damage response was triggered in SUN1-depleted oocytes and thus gave rise to the G2/M checkpoint protein, p-CHK1. Oocytes that underwent GVBD had relatively small and abnormal spindles and lower levels of cytoplasm F-actin mesh. Immunofluorescence results also indicated the dislocation of pericentrin and P150(Glued) after SUN1 or KASH5 depletion. Furthermore, KASH5 localized exclusively near the oocyte cortex after SUN1 depletion, but SUN1 localization was unaffected in KASH5-depleted oocytes. Taken together, the results suggest that SUN1 and KASH5 are essential factors in the regulation of meiotic resumption and spindle formation.